Treating depression in dialysis patients: pharmacological and non-pharmacological approaches - Daniel Cukor; Christian Cornelius; Kate Dahl; Daniela Figueiredo; Helena Sousa; Ava Archey; Paul L Kimmel (Clinical Kidney Journal, 2026)
Abstract Depression is relatively common in patients with kidney failure treated with hemodialysis, and the prevalence rate exceeds that of the general population. Depression should be treated in people maintained on dialysis, both due to depression’s inherent significance and its potential complications for kidney treatment. This paper reviews the relevant literature on reported pharmacological and non-pharmacological approaches. Although the evidence base is somewhat limited, recent clinical trials have allowed formulation of practical treatment recommendations. The literature on pediatric CKD is also reviewed. Although the evidence base is scarce, treatment recommendations for the pediatric population are discussed. Various barriers to the integration of standardized depression screening and treatment for people with kidney failure treated with hemodialysis are reviewed.